Bario Community Radio: Engaging people making news - Mus Chairil, Samani; Poline, Bala; Jamilah, Maliki; Harris, Roger W. (2013)
Bario Community Radio went on air in October 2011. Its intended public is the Kelabit people who are living within the 25-kilometer radius from the broadcast facility located at e-Bario telecentre. The station is administered by a manager who also serves as the broadcast journalist and radio announcer. He is assisted by two other broadcasters. The radio is broadcasted twice each day: two hours in the morning and two hours in the evening. A survey was conducted to assess the impact of the radio on the Kelabit community living in Bario. A total of 61 people participated in a survey that was conducted in December 2012. The findings indicate that the radio broadcast is well received by the community. Most of them are tuning in to the morning radio broadcast. The most sought information by the listeners on the radio is the national and community news. The national news read over the radio are obtained from the mainstream online newspapers. The community news is provided by the listeners who would pass the information to the station manager for broadcast.